Adorno v Československu: hudba, teória, estetika - Fulka, Vladimír (. Ensayos sobre política económica. - Bogotá, 1982-. - Online-Ressource. - ISSN 0120-4483 9, 2020)
The aim of this paper is to examine how Adorno's aesthetic and musicological thinking was received in Czech and Slovak musicology in the decades between the 60s and the 80s. The focus is on the Czech and Slovak translation of some of Adorno’s musicological treatises and lectures – especially those concerning his views on the Second Vienna School and the musical poetics of its immediate successors – which were published in former Czechoslovakia. The study offers an interesting perspective on Adorno’s relatively unknown lecture Form der neuen Musik (1965) and its related, although not identical, Czech version Formové princípy súčasnej hudby [Formal Principles of Contemporary Music] (1966) as well as on his discussion with some Slovak composers and musicologists published as Dnes je možné iba radikálne kritické myslenie [Today, Only Radical Critical Thinking is Possible] (1967). The study also considers other scientific texts by Adorno in relation to the above-mentioned translations of his works. The analysis, reflection, and interpretation of Adorno’s works in former Czechoslovakia, as well as their contemporary reception, turn out to be sporadic in the examined period. The purpose of this research is to revive awareness of their significance and to give a new impulse to their reassessment within the current musicological and philosophical reflection.